The rise of a new competitive intelligence: need of real-time competitive intelligence and the impact on decision-making - Gundersen, Sofie Hildal (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence